Accelerating chemical reactions by molecular sledding. Issue 47 (26th May 2017) - Zhang, Lei; Zheng, Lifei; Meng, Zhuojun; Balinin, Konstantin; Loznik, Mark; Herrmann, Andreas
Abstract : The speed-up of covalent bond formation and cleavage were both achieved by utilizing sliding peptide-modified functionalities moving on DNA. Abstract : The speed-up of covalent bond formation was achieved between a sulfhydryl group and a 2-bromopropionic acid derivative by utilizing sliding peptide-modified substrates. Moreover, a new type of DNA cleaving reagent was developed, consisting of pVIc covalently coupled to verteporfin. This peptide–porphyrin conjugate allowed targeting of DNA and resulted in increased photodegradation of double-stranded nucleic acids.